Physicochemical property, volatile flavor quality, and microbial community composition of Jinhua fatty ham and lean ham: A comparative study - Zhang, Jin; Zhao, Ke; Li, Huanhuan; Li, Shuangxi; Xu, Weimin; Chen, Lihong; Xie, Jing; Tang, Honggang (Frontiers in Microbiology, 2023)
The physicochemical property, volatile flavor compounds, and microbial community structure of Jinhua fatty ham (FH) and lean ham (LH) were investigated and compared by high-throughput sequencing and HS-GC-IMS. Results showed that FH had higher pH and slightly lighter and yellower color than LH. Meanwhile, 33 volatile flavor compounds were identified from FH and LH, among which LH showed higher abundance of total alcohols and acids, but FH had generally richer aldehydes, ketones, esters, heterocyclic, and sulfur-containing compounds. Moreover, FH and LH didn’t have significant difference in α-diversity of bacterial community, but LH presented a much lower α-diversity of fungal community than FH. Besides, the dominant microorganisms (relative abundance >2%) in FH were Ruminococcaceae UCG-005, Staphylococcus, Ruminococcaceae UCG-014, Meyerozyma, and Aspergillus at the genus level, while in LH were Staphylococcus, Psychrobacter, Halomonas, Propionicicella, Ruminococcaceae UCG-005, Meyerozyma, Yamadazyma, and Aspergillus. Furthermore, the analysis of Pearson’s correlation and metabolic network confirmed that the discriminative flavor compounds of FH were mainly β-oxidation and degradation products of fatty acids, while those of LH were mostly derived from the Strecker reaction or microbial metabolism of amino acids. The present study could help understand the potential pathway of characteristic microorganisms affecting flavor formation of fat-deficient dry-cured hams and provide theoretical supports for developing healthier fermented meat products.